If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying A + 14 = -3 Reorder the terms: 14 + A = -3 Solving 14 + A = -3 Solving for variable 'A'. Move all terms containing A to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + A = -3 + -14 Combine like terms: 14 + -14 = 0 0 + A = -3 + -14 A = -3 + -14 Combine like terms: -3 + -14 = -17 A = -17 Simplifying A = -17
| 3-6y=0 | | f(n)=3f(n-1)+2 | | 288=18v | | n/2,400=5 | | 6m-3=3m+24 | | 0.071(-71.3)(x)+0.1(4.3)+0.059(0.22)(4.3)=0 | | B-(-2)=19 | | 5+2timesg=20 | | q-2=2 | | 40a^4-5a= | | 7y-1f=17 | | 4(y-7)=3(6+2y) | | -41=4-9r | | -x=-7x+16 | | 5b/32a2= | | y-2.3=8 | | 5/30=1x | | 180=4x+112 | | 5x-6=-2x+1 | | y+3.4=6 | | m-(-5m)-2+3m=-29 | | 3(3s+1)=2(4s+2) | | m=3/4(2,1) | | X+(-14)=-15 | | 6=m-7.8 | | x^3-17x^2+92x-160=0 | | 1/3y=2(x-1/6) | | -4=x+8-3x | | 114=6(6b-5) | | -2/7x=14 | | 3n+20=32 | | 1yo+1ma+1ma=1de+1ez+1nuts |